Morpho-semantic analysis of contemporary Swahili speakers’ linguistic innovations on microloan names - Emmanuel Ilonga (Cogent Arts & Humanities)
Many studies on names have investigated the naming of people, plants, places, and inscriptions on transport facilities. However, very little is currently known about the naming of microloans, their connotations, and morphology. This article studied the Swahili speakers’ construct and connotations of microloan names in Tanzania. Data for this article was randomly generated from social media platforms, online newspapers, YouTube TV channels, and interviews with some debtors. Drawing on onoma-pragmatic approach in the semantic analysis of data, the findings show that the microloan names connote loan disbursement, loan repayment, loan goals, and loan adversities. Regarding the shapes of the microloan names, compounding, associative constructions, context-borrowing, and reduplication methods are the notable linguistic methods employed in the creation of the loan names. Essentially, this article unveils the Swahili speakers’ linguistic innovations on the creation and semantic connotations of the microloan names which reflect diverse experiences. Furthermore, it calls for the respective authorities to regularly review the interest rates charged by informal credit providers so as to create favourable conditions for both—moneylenders and borrowers.